Effect of Turmeric Ethanol Extract (Curcuma Longa Linn) on IL-6, IL-10 Levels and Skin Moisture - Anggraeni, Gilda Putri; Sumarawati, Titiek; Chodidjah; Wibowo, Joko Wahyu; Zulaikah, Siti Thomas; Trisnadi, Setyo (Gema Lingkungan Kesehatan, 2025)
Ultraviolet B (UVB) radiation is known to induce skin damage, including erythema, roughness, sagging, wrinkles, and reduced skin moisture, contributing to premature aging. Turmeric (Curcuma longa Linn.) contains curcumin, an active compound with potent anti-inflammatory properties. This study investigated the effect of turmeric ethanol extract on IL-6 and IL-10 levels, as well as skin moisture, in UVB-exposed rats. A total of 24 Wistar rats were randomly divided into four groups: healthy controls (K1), UVB-exposed without treatment (K2), UVB-exposed treated with turmeric ethanol extract at 100 mg/kg BW (K3), and 200 mg/kg BW (K4). The extract was administered orally for 14 days. IL-6 and IL-10 levels were measured using ELISA, and skin moisture was assessed macroscopically. Statistical analysis was performed using one-way ANOVA. Rats in groups K2, K3, and K4 exhibited very dry skin, redness, visible wrinkles, and peeling following UVB exposure. IL-6 levels were significantly lower in treated groups, with the lowest levels observed in K4 (1.85 ± 0.24 ng/L), compared to K1 (4.36 ± 0.75 ng/L) and K2 (4.46 ± 0.74 ng/L) (p = 0.000). IL-10 levels increased in the treated groups, notably in K3 (376.48 ± 78.24 pg/mL) and K4 (351.06 ± 78.24 pg/mL), compared to K1 (285.34 ± 45.54 pg/mL) and K2 (306.89 ± 45.54 pg/mL) (p = 0.001). These findings suggest that oral administration of turmeric ethanol extract modulates inflammatory responses by reducing IL-6 and enhancing IL-10 in UVB-exposed skin, although significant dryness persists.